2015
DOI: 10.1111/anu.12383
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of soybean coproducts in extruded diets for Nile Tilapia,Oreochromis niloticus

Abstract: Soybean coproducts are important protein sources in aquaculture because of their amino acid profile. Tilapia can be reared on soybean coproducts as the only source of dietary protein without compromising growth. This study estimated apparent digestibility coefficients for five soybean coproducts for juvenile Nile tilapia, Oreochromis niloticus, fed with extruded diets. A reference diet and test diets consisting of 70% reference diet and 30% coproduct ingredient were formulated, along with 5.0 g kg À1 chromic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
3
15
1
Order By: Relevance
“…When replacing animal ingredients by plant‐based ingredients, fish can get exposed to ‘foreign’ components like starch and anti‐nutritional factors that can interfere with the natural processes occurring in the intestine (Steiner & Encarnacão, ). Several reviews addressed the fish meal replacement by plant protein in Nile tilapia diets (Figueiredo‐Silva, Lemme, Sangsue, & Kiriratnikom, ; Tram et al, ; Vidal et al, ; Zhou & Yue, ). Recently, Tran‐Ngoc et al () showed that SBM in combination with an environmental stressor challenge affected the intestinal morphology of Nile tilapia, but information is lacking and how other plant‐based ingredients alter intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When replacing animal ingredients by plant‐based ingredients, fish can get exposed to ‘foreign’ components like starch and anti‐nutritional factors that can interfere with the natural processes occurring in the intestine (Steiner & Encarnacão, ). Several reviews addressed the fish meal replacement by plant protein in Nile tilapia diets (Figueiredo‐Silva, Lemme, Sangsue, & Kiriratnikom, ; Tram et al, ; Vidal et al, ; Zhou & Yue, ). Recently, Tran‐Ngoc et al () showed that SBM in combination with an environmental stressor challenge affected the intestinal morphology of Nile tilapia, but information is lacking and how other plant‐based ingredients alter intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of tilapia, a wealth of alternative protein sources is available and in use. For some of these ingredients, the apparent nutrient digestibility has been reported already, for example, cottonseed meal and sunflower meal (SFM; Aanyu, Ondhoro, Ganda, Kato, & Basiita, ; El‐Saidy & Gaber, ), feather meal (Guimarães, Pezzato, & Barros, ), dried distillers grains with solubles (DDGS) (Schaeffer, Brown, Rosentrater, & Muthukumarappan, ), rice bran (RB) (Guimarães, Pezzato, Barros, & Tachibana, ), rapeseed (Borgeson, Racz, Wilkie, White, & Drew, ) and soybean meal (SBM) (Koch et al, ; Lin & Luo, ; Vidal et al, ). The substitution of fish meal coincides with an increased variability in dietary nutrient/ingredient composition.…”
Section: Introductionmentioning
confidence: 96%
“…It is necessary to meet the optimal requirements of all essential amino acids in aquafeeds, because deficiency in one may cause impaired utilization of the other amino acids, and protein synthesis will be negatively affected. In recent years, available amino acids' values of many feed ingredients have been addressed for Nile tilapia (Guimarães, Pezzato, & Barros, ; Guimarães, Pezzato, Barros, & Tachibana, ; Vidal et al., , ; Xavier, Michelato, Vidal, Furuya, & Furuya, ), in order to elaborate more precise diets to maximize dietary nitrogen utilization and improve sustainability of farmed fish. Moreover, dietary requirements should be determined based on available amino acids, to formulate oriented environmental diet because the availability coefficients of amino acids are quite variable among feeds (Guimarães, Pezzato, & Barros, ) and fish species (NRC, ).…”
Section: Introductionmentioning
confidence: 99%
“…For some of these ingredients, the apparent nutrient digestibility has been reported already, e.g. cottonseed meal and sunflower meal Gaber, 2003, Aanyu et al, 2014), feather meal (Guimarães et al, 2008a), dried distillers grains with solubles (DDGS) (Schaeffer et al, 2010), rice bran (Guimarães et al, 2008b), rapeseed (Borgeson et al, 2006), and soybean meal (SBM) (Lin and Luo, 2011, Vidal et al, 2015, Koch et al, 2016. The substitution of fish meal coincides with an increased variability in dietary nutrient/ingredient composition.…”
Section: Introductionmentioning
confidence: 88%
“…When animal protein ingredients are replaced by plant-based ingredients, fish get exposed to a series of "foreign" components such as starch and anti-nutritional factors that can interfere with the natural processes occurring in the intestine (Steiner and Encarnacão, 2010). In Nile tilapia, several reviews have dealt with the subject of replacing fish meal by plant protein based diets (Tram et al, 2011, Zhou and Yue, 2012, Vidal et al, 2015, Figueiredo-Silva et al, 2015, and more recently, Tran-Ngoc et al (2016a) showed that soybean meal combined with an environmental factor had negative effects on the intestinal morphology of Nile tilapia, but the information regarding how the intestinal morphology is affected by other plant-based ingredients is still scare.…”
Section: Intestinal Morphologymentioning
confidence: 99%